Association between ankle sprain history and ankle sprain incidence in national basketball association games - Herzog, M.; Mack, C.; Dreyer, N.; Wikstrom, E.; Padua, D.; Kocher, M.; Marshall, S. (British Journal of Sports Medicine, 2021)
Background Ankle sprains have one of the highest recurrence rates among all lower extremity injuries in sports.